İstanbul’daki ortaöğretim kurumlarında afet ve acil durum hazırlklarının değerlendirilmesi - Kökcü, Aysel (My University, 2010)
İstanbul’daki Ortaöğretim Kurumlarında Afet ve Acil Durum Hazırlıklarının Değerlendirilmesi Bu çalışma, İstanbul’daki ortaöğretim kurumlarında afet ve acil durum hazırlıklarını, değerlendiren bir ölçüm aracı geliştirmek amacıyla metodolojik, ortaöğretim kurumlarında en çok hangi tür afet/ acil durumlara rastlanma olasılığını, afetlere ve acil durumlara karşı yapılan hazırlıkları ve okullar arasındaki farklılıkları tespit etmek amacıyla tanımlayıcı olarak yapıldı. Araştırma; İstanbul’da bulunan 150 resmi ve özel ortaöğretim kurumundaki 2500 yönetici ve çalışanla yapıldı. Veriler araştırmacı tarafından geliştirilen 253 soruluk “Ortaöğretim Kurumlarında Afet ve Acil Durum Hazırlıklarını Değerlendirme Formu” ile toplandı (Cronbach Alpha=0.97). Araştırma kapsamındaki okulların, afet ve acil durumlara hazırlıksız oldukları belirlendi. Okullarda afet/ acil durumlara yönelik hazırlıklara çalışanların aktif katılmadıkları, kurumlararası koordinasyon ve işbirliğinin yetersiz olduğu, eğitimlerin okul toplumunu kapsamadığı, tatbikatların düzenli olarak yapılmadığı, ilkyardım konusunda çalışanların kendilerini yetersiz hissettikleri, Özel Türk Orta Öğretim Kurumları dışında okullarda sağlık profesyonellerinin bulunmadığı, okulların çoğunda acil haberleşme sisteminin olmadığı, yapısal hasara bağlı gerekli tedbirlerin ve lojistik hazırlıkların yetersiz olduğu belirlendi. Özel Türk Ortaöğretim Kurumlarının afet/ acil durumlara diğer okullardan daha hazırlıklı oldukları saptandı. Bu sonuçlar; İstanbul’da meydana gelecek büyük bir afet/ acil durumda okullarda bulunan öğrenci/ çalışan, mekan/ mülk ve eğitimin olumsuz etkileneceğini, okullarımız ve yetkili kurumlarımız tarafından oluşturulacak planlar doğrultusunda, ivedilikle bireysel ve kurumsal hazırlıkların yapılması gerektiğini göstermektedir. Durum, Afet, Hazırlık, Ortaöğretim.

An Evaluation of the Emergency and Disaster Preparedness in High Schools in Istanbul This study was carried out; as a methodological research to evaluate emergency and disaster preparedness in high schools in Istanbul and as a descriptive research to determine which disasters or emergency situations are the most probable in high schools, and to determine disaster and emergency preparedness in schools and differences between schools. The sample and universe for the study consisted of 2500 employees and administrators working in various positions in 150 private and public high schools in Istanbul. To collect data for the research; A Questionnaire Form for Emergency and Disaster Preparedness in Schools- a 253 item data collection instrument prepared by the researcher- was used (Cronbach Alpha=0.97). The schools in the coverage of the study were found to be unprepared for emergencies and disasters. It was found that employees in the schools did not actively participate in the preparations for emergencies and disasters, and the coordination and cooperation between institutions was inefficient, and training activities did not involve school society, and the exercises were not done regularly, and employees felt themselves inefficient to give first aid, and there were no health professionals in schools except Private Turkish High Schools, and there were no emergency communication systems in most of the schools covered, and necessary measures and logistical preparedness based on building site damages were inadequate. Private Turkish High Schools were found to be more prepared for emergencies and disasters than the other schools covered. These results show that; employees, students, and employees working in schools, and the school buildings, and education will be negatively affected in a probable major disaster or emergency situation in Istanbul, and individual and institutional preparations should be done urgently according to a plan prepared by our schools and authorized institutions. Key words: Emergency, Disaster, Preparedness, High School.
Keywords: Afet; Afet Planlaması; Ortaöğretim_Afet Planlaması